Job Satisfaction : Peran Gaya Kepemimpinan - Ananda Kharismatika; Anwar Mansyur (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study examines the influence of three leadership styles on employee job satisfaction in manufacturing companies in Kendal Regency. The research focuses on spiritual leadership, servant leadership, and inclusive leadership as independent variables that potentially affect job satisfaction as the dependent variable. Using a quantitative approach with simple random sampling, data were collected from manufacturing company employees through questionnaires measured on a Likert scale. Data analysis was conducted using SPSS Statistics, including validity tests, reliability tests, coefficient of determination tests, F-tests, and hypothesis testing. The results reveal that spiritual leadership and servant leadership do not have significant positive effects on job satisfaction, while inclusive leadership demonstrates a significant positive effect on job satisfaction. The coefficient of determination indicates that the three leadership styles explain a portion of the variance in job satisfaction, while the remainder is influenced by other factors not examined in this study. These findings provide practical implications for organizational leaders in selecting and developing appropriate leadership styles to enhance employee job satisfaction in manufacturing environments.